1999
DOI: 10.1037/h0080410
|View full text |Cite
|
Sign up to set email alerts
|

The National Lesbian Family Study: 2. Interviews with mothers of toddlers.

Abstract: In this second report from a longitudinal study of lesbian families in which the children were conceived by donor insemination, interviews yielded the following data: Most couples shared parenting co-equally; the majority felt closer to their family of origin; adoptive co-mothers felt greater legitimacy as parents; biology and nurture received the same ratings for mother-child bonding; and political and legal action had increased among many participants. The impact of these findings and that of homophobia on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
236
0
15

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(256 citation statements)
references
References 19 publications
5
236
0
15
Order By: Relevance
“…This phenomenon provides a rich opportunity for social scientists to study the well-being of teenagers who have been raised since birth in what is known as planned lesbian families. 8,[19][20][21][22][23][24][25][26][27] Psychosocial research on young children in planned lesbian families has focused primarily on 4 key developmental outcomes: psychological adjustment, peer relationships, family relationships, and progress through school. 8,14,15,28 In young children, adjustment is largely determined by family functioning: regardless of their parents' gender or sexual orientation, children fare better when their parents are compatible, share responsibilities, provide financial stability, and have healthy interpersonal connections.…”
mentioning
confidence: 99%
“…This phenomenon provides a rich opportunity for social scientists to study the well-being of teenagers who have been raised since birth in what is known as planned lesbian families. 8,[19][20][21][22][23][24][25][26][27] Psychosocial research on young children in planned lesbian families has focused primarily on 4 key developmental outcomes: psychological adjustment, peer relationships, family relationships, and progress through school. 8,14,15,28 In young children, adjustment is largely determined by family functioning: regardless of their parents' gender or sexual orientation, children fare better when their parents are compatible, share responsibilities, provide financial stability, and have healthy interpersonal connections.…”
mentioning
confidence: 99%
“…It is also likely that lesbian social mothers feel pressured to be visible as a mother (De Kanter, 1996;Muzio, 1999, Nekkebroeck & Brewaeys, 2002, because they think that their position is different from that of lesbian and heterosexual biological parents. Other studies (e.g., Gartrell et al, 1999) have shown that although social mothers consider themselves to be equal parents, they display feelings of jealousy and competitiveness concerning child rearing issues. Social mothers indicate that, in their view, the biological tie is an important factor affecting mother-child attach-ment.…”
Section: Family Characteristicsmentioning
confidence: 99%
“…Adolescence is a time during which teenagers are particularly sensitive to disapproval from peers (Rubin et al 2006). Because lesbian mothers anticipate that their offspring may be subjected to homophobic stigmatization, protective responses include careful supervision of their offspring's routine activities and leisure time (Gartrell et al 1999(Gartrell et al , 2000. As their offspring enter adolescence, it is not known whether lesbian parents extend this monitoring to impose even stricter controls than heterosexual parents.…”
Section: Introductionmentioning
confidence: 99%